KH. SHOLAHUDDIN WAHID STRATEGY IN INCREASING THE COMPETITIVE ADVANTAGE OF PESANTREN TEBUIRENG, JOMBANG, EAST JAVA - Luqman, Asaduddin; Suyudi, M.; Husen Ismail, Faisal; Marpuah, Siti (Jurnal 'Ulwan, 2025)
This research aims to find out what KH. Salahuddin Wahid's public interest in sending his children to the Tebuireng Islamic boarding school continues to increase. This research is a literature study using content analysis. KH. Sholahuddin Wahid chose efforts to increase the competitive advantage of the Tebuireng Islamic boarding school to focus on two things. First, the physical construction of the Tebuireng Islamic boarding school complex includes a dormitory for students to live in, a mosque, and other supporting facilities. Second, students should strengthen their mastery of kitab kuning. One of them is by reopening Mu'allimin and reviving the Madrasah Diniyah so that Tebuireng students have the ability to read and understand kitab kuning as characteristic of pesantren salafiyah.